2020
DOI: 10.1021/acsami.9b21391
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nanoconfinement on Polylactide Crystallization and Gas Barrier Properties

Abstract: The barrier properties of poly(L-lactide) (PLLA) were investigated in multinanolayer systems, probing the effect of confinement, the compatibility between the confining and the confined polymer, crystal orientation, and amorphous phase properties. The multilayer coextrusion process was used to confine PLLA between two amorphous polymers (polystyrene, PS; and polycarbonate, PC), which have different chemical affinities with PLLA. Confined PLLA layers of approximately 20 nm thickness were obtained. The multinano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…In fact, in multilayered structures by nanoscale confinement, the polymer layers crystallized as single crystals in in-place orientation parallel to the layers. More recently, the confinement of PLLA by PC and PS amorphous polymer layers have been performed by means of the multilayer coextrusion process [15], and the authors have highlighted the impact on the oxygen barrier properties of the rigid amorphous fraction (RAF) generated by postannealing of the multilayer films. Annealing PLLA/PS films allowed for obtaining a high crystallinity degree without RAF and this has induced an oxygen barrier improvement by a factor of 10 with 20 nm thick PLLA layers [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in multilayered structures by nanoscale confinement, the polymer layers crystallized as single crystals in in-place orientation parallel to the layers. More recently, the confinement of PLLA by PC and PS amorphous polymer layers have been performed by means of the multilayer coextrusion process [15], and the authors have highlighted the impact on the oxygen barrier properties of the rigid amorphous fraction (RAF) generated by postannealing of the multilayer films. Annealing PLLA/PS films allowed for obtaining a high crystallinity degree without RAF and this has induced an oxygen barrier improvement by a factor of 10 with 20 nm thick PLLA layers [15].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the confinement of PLLA by PC and PS amorphous polymer layers have been performed by means of the multilayer coextrusion process [15], and the authors have highlighted the impact on the oxygen barrier properties of the rigid amorphous fraction (RAF) generated by postannealing of the multilayer films. Annealing PLLA/PS films allowed for obtaining a high crystallinity degree without RAF and this has induced an oxygen barrier improvement by a factor of 10 with 20 nm thick PLLA layers [15]. Concerning the water barrier properties for multilayer films, nowadays, only few works refer to this and the water barrier improvement was mainly obtained afterheat treatment or after a biaxial drawing [16] utilized to promote polymer crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…The intermolecular interaction between PLA chains has been utilized to improve the interfacial interaction between the n-HA filler and PLA matrix; generally, PLA oligomers are grafted onto n-HA to achieve better dispersion in the PLA matrix and improve the mechanical propertie It has been reported that stereocomplex could form between enantiomeric poly(L-lactide) (PLLA) and poly(D-lactide) (PDLA) in solution, oriented drawing, interface, hot drawing, and even during 3D printing [30][31][32][33][34]; the stereocomplex produces numerous dense, micron-sized crystals that act as cross-linking points between polymer chains and connect the high-density "tie chains" between crystals, thereby significantly improving the mechanical properties [35]. The tensile strength and Young's modulus of PDLA/PLLA blend films are at least 30% higher than those of the corresponding pure PLLA films in almost any molecular weight rang The presence of stereocomplex crystals in the PLA matrix not only improves the mechanical properties but also enhances the crystallinity and thermal stability [36].…”
Section: Introductionmentioning
confidence: 99%
“…For thicker layers ( 100 nm), confined spherulite morphologies that increase the tortuosity for gas diffusion have been observed for high density polyethylene (HDPE) confined against a cyclic olefin copolymer (COC) [17]. In addition to crystal orientation, other parameters may have a strong influence on the barrier properties, such as the crystal phase [18] or the amorphous phase that can be constrained [14,19,20] and/or oriented [21].…”
Section: Introductionmentioning
confidence: 99%